P2_3 Firing from the Gulf - Dangerfield, Kyle; Walton, Samuel; Lewis, Elspeth; Byrne, Jamie (Physics Special Topics, 2017)
In the 2009 lm Transformers: Revenge of the Fallen, a railgun is red from the Gulf of Suez to the top of the Great Pyramid of Giza in approximately 5 seconds. We consider parabolic motion to calculate the muzzle velocity of the projectile to be 28000 ms^(-1). We then calculated the acceleration and the necessary force required within the railgun. Finally, the energy required to achieve the desired result was found to be 1.96x10^9 J.